An Approach to Distribution System Planning by Implementing Distributed Generation in a Deregulated Electricity Market - Porkar, S.; Abbaspour-Tehrani Fard, A.; Saadate, S. (2007 Large Engineering Systems Conference on Electric Power Engineering, 2007)
Electric power deregulation has drastically affected the engineering aspects of planning. In addition need flexible electric systems, changing regulatory and economic scenarios, energy savings and environmental impact are providing impetus to the development of distributed generation (DG), which is predicted to play an increasing role in the electric power system of the future. This opens the venue for distribution company's (disco) aiming to minimize their investment risks by developing optimum new planning strategies to meet the load growth and satisfy the system performance at minimum cost different electricity structures. This paper proposes a framework for solving the distribution system planning (DSP) problem by implementing DG from the perspective of a disco. The proposed model employs integer decision variables to achieve optimal sizing and siting of DG. This model aims to minimize DG's investment and operating costs, total payments toward compensating for system losses along the planning period, as well as purchasing power from an existing grid to meet the load demand growth according the present worth analysis to introduce DG as a key element in solving the DSP problem. In this paper it is also compared five type of DG technology to determine which technology is best suited to meet specific energy needs in a case study.